ROLE OF LOW DOSE ASPIRIN FOR PREVENTION OF PRE-TERM BIRTH IN PREGNANT WOMEN WITH PREVIOUS HISTORY OF PRE-TERM LABOR - Maqsood, Sumaira; Iqbal, Madiha (Khyber Journal of Medical Sciences, 2025)
Objective: To evaluate the role of low-dose aspirin in preventing preterm births in pregnant women with a history of preterm labor. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Obstetrics and Gynaecology, MTI-HMC Peshawar, from 18th Sep 2024 to 18th Mar 2025. Methodology: A total of 384 pregnant women with a history of preterm labor and gestational age between 6 and 20 weeks were included. Participants were allocated into two groups through a non-random sequential allocation method designed to ensure comparable group sizes. Women in Group A received 75 mg of low-dose aspirin daily until 37 weeks of gestation, while those in Group B received placebo. All analyses were performed using SPSS version 26.0. The chi-square test, with a p-value <0.05, is considered statistically significant. Results: The mean age was 30.01 ± 6.34 years in Group A and 28.98 ± 6.64 years in Group B, with similar parity. The mean gestational age at delivery was 33.41 ± 4.93 weeks in Group A and 27.40 ± 4.32 weeks in Group B. Preterm birth occurred in 20.3% of Group A compared to 81.3% of Group B (p < 0.001). The mean APGAR score at 1 minute was 8.04 ± 0.81 in Group A and 2.46 ± 1.76 in Group B, while at 5 minutes it was 8.41 ± 0.49 and 3.08 ± 1.96, respectively (p < 0.001). Conclusion: Low-dose aspirin significantly reduces preterm birth rates and improves neonatal outcomes, including APGAR scores and NICU admissions.